Construcción integral de una cultura de aprovechamiento de residuos solidos en el sector residencial de la Localidad de Suba, Bogotá (2020)
This project seeks to contribute by creating a positive change in solid waste management in the city of Bogotá, Colombia within the residential sector. For this, a study is carried out in the most populated locality of this city, the locality of Suba. In the first measure, the most representative challenges were identified, such as the deficiency of the public service in the cleaning service, because its only focus is to collect and transport more, not to separate, on the other hand, also as a challenge, we find that there is no culture of exploitation, but of mass consumption. Once the above challenges had been considered, the actors that participate in this work of waste management in the residential sector were identified, recognizing as main actors the residents, horizontal property managers and cleaning and security personnel. In order to develop a more direct and reliable investigative process, stratum five (5) was determined as the most suitable within the residential sector chosen to carry out this study and evaluation, because it presents the highest waste production. The approach and research was developed using the survey technique; allowing to collect relevant information, and apply participatory methods in educational processes, which give way to the creation of new beliefs by generating awareness, and therefore generating changes in behaviors and habits of solid waste disposal. This process began with a pilot test in a household of four members of a family in the sector, who were given an educational and training process that when validating the information was integrated into a series of three videos that seek to raise awareness and generate a change based in the information collected from the surveys and thus share this information within a stratum five residential complex, to make a complete test of a residential community.